Premixed combustion of coconut oil in a hele-shaw cell - Saroso, Hadi; Wardana, I.N.G.; Soenoko, Rudy; Hamidi, Nurkholis (Center of Biomass & Renewable Energy, Diponegoro University, 2014)
Coconut oil combustion characteristic is observed experimentally by evaporating oil in the boiler then mix it with air before being burned at various equivalence ratios in the Hele-shaw cell. The result shows that, coconut oil tends to break into glycerol and fatty acid due to hydrolysis reaction producing the flame propagation, where the fatty acid flame propagates first then glycerol flame. Micro-explosion occurs when moisture from fatty acid combustion is absorbed by glycerol and higher heating due to higher flame speed produces more micro-explosion.